Nomadism, Foreigners, Possible Homelands: Roberto Bolaño's Narrative Between two Continents (Anclajes, 2021)
The posthumous work of Roberto Bolaño presents the intriguing theme of national identity and immigration. This work analyzes the difficult and ambivalent relationship that Chilean characters establish with their homeland then shows how the protagonists’ life circumstances lead to an eternal nomadism. It then considers the relationship the characters establish with Latin America, revealed to be the only possibility for belonging. The posthumous work of Roberto Bolaño presents the intriguing theme of national identity and immigration. This work analyzes the difficult and ambivalent relationship that Chilean characters establish with their homeland then shows how the protagonists’ life circumstances lead to an eternal nomadism. It then considers the relationship the characters establish with Latin America, revealed to be the only possibility for belonging. The article closes with a reflection on the importance of literature in the life of Bolaño’s characters.
Keywords: Chilean narrative; Roberto Bolaño; 21st century; literary analysis